Accelerating AXL targeting for TNBC therapy. (October 2021) - Khera, Lohit; Lev, Sima
Highlights: AXL facilitates migration, invasion, EMT, stemness and metastasis of TNBC. AXL is involved in resistance to various anti-cancer therapies. Targeting of AXL could be effective for a subset of breast cancer patients. Targeting of AXL in combination with other anti-cancer drugs has clinical potential. Preclinical studies and modeling can improve therapeutic strategies targeting AXL. Abstract: The tyrosine kinase receptor AXL of the TAM (TYRO3, AXL and MERTK) family is considered as a promising therapeutic target for different hematological cancers and solid tumors. AXL is involved in multiple pro-​tumorigenic processes including cell migration, invasion, epithelial-mesenchymal transition (EMT), and stemness, and recent studies demonstrated its impact on cancer metastasis and drug resistance. Extensive studies on AXL have highlighted its unique characteristics and physiological functions and suggest that targeting of AXL could be beneficial in combination with chemotherapy, radiotherapy, immunotherapy, and targeted therapy. In this mini review, we discuss possible outcomes of AXL targeting either alone or together with other therapeutic agents and emphasize its impact on triple negative breast cancer (TNBC).